Additional Income : Concepts and Efforts in Improving Motivation of Employment Civil Services as Step to Make Agood Governance - Ichsandria Erdinal (International Conferences on Educational, Social Sciences and Technology)
The rapid development in the era of globalization and complex problems faced by the State in line with the development of governance to realize good governance. Good governance is a prerequisite to realize the desire of the community in achieving the goals of nation and state. Implementation of the concept of good governance has its own challenges, for it needed resources apparatus that have competence in running government administration and sustainable development. To create competent apparatus that is efficient, effective, clean, strong and authoritative and able to carry out general duties of government and development as well as possible, it is necessary to improve quality and work motivation. In order to improve the quality and motivation of work it is necessary to provide additional income employee to Civil State Apparatus.